Dreams as Narrative Pullers: A look into Buddhadeb Dasgupta’s National award winning films ‘Mondo Meyer Upakhyan’ and ‘Kalpurush - Sudheer S. Salam (COMMUNICATION & JOURNALISM RESEARCH, 2012)
Eminent film makers have used many of the unreciprocated phenomena’s of human life as a device to construct their quality narratives. Buddhaded Dasgupta’s use of dreams (rather than dreaming sequences) as a device to pull off his narratives needs a special mention , for it is holding power of the central premises and establishing lucid presentations, also making the distinction between manifestations and reality. An analysis of his placement of dreams to the central characters also gives us a picture of how effectively he uses it as a metaphor of emerging culture and human conditions as a whole. The present article is an exploration of how the diverse characters of Dasgupta’s films- ‘Mondo Meyer Upakhyan’ and ‘Kalpurush’ are loaded with pivotal dreams that force them to jump out of their existential problems, thereby acting as able narrative pullers.